ANTARA KETELADANAN DAN MOTIVASI BELAJAR; PENGARUH DARI KOMPETENSI KEPRIBADIAN GURU DI MTS AZIDDIN MEDAN (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Teachers are required to have four competencies in carrying out education. The four competencies are closely related to the quality of education. This study highlights one of four competencies, namely personality competence. The purpose of this study is to see how much influence the teacher's personal competence on student motivation. This type of research is an associative research with a quantitative approach. This study uses simple regression analysis to see the effect of variable (X) on variable (Y). The results showed that the influence of teacher personality competencies on student motivation. Although the effect is not strong, but it concludes that one way to increase student motivation is to improve the teacher's personal competence.